Prototype Design of Air Quality Control Blower at PT SINAR INDOGREEN KENCANA Production Area - Prayudha, Mufit Yogie; Sulistiyowati, Indah; Saputra, Dwi Hadidjaja Rasjid (Buletin Ilmiah Sarjana Teknik Elektro, 2024)
PT SINAR INDOGREEN KENCANA is a company that produces AAC (Autoclave Aerated Concrete) lightweight bricks, the existence of a limestone grinding machine (Mill MTW) into lime powder and maturation of raw materials with the steam process of the autoclave machine, as well as the occurrence of rain that disrupts air circulation in the production area, causing a lot of dust and hot water vapor from the machining process to enter the production area, thus disrupting the performance of employees. This research aims to design a prototype blower for air quality control in the production area of PT SINAR INDOGREEN KENCANA. Where this system is designed to control and monitor dust and temperature levels, utilizing ESP8266 as a monitoring unit and Arduino UNO as a controller, with Blynk integration as a user interface. In operation, ESP8266 monitors dust levels and temperature through the I2C LCD, turning on the blower to suck dust and water vapor from the remaining hot production. Arduino UNO as a link between the GP2Y1010AU0F sensor for dust detection and the DHT22 sensor for temperature detection, sends data on dust levels and temperature to ESP8266. Through the BLYNK application, users can find out dust levels, temperature, and whether the blower is on or off. The application of this system obtained the result that the whole system provides an integrated and effective solution for controlling air quality in the production area of PT SINAR INDOGREEN KENCANA.